Evaluation of starches obtained from four dioscorea species as binding agent in chloroquine phosphate tablet formulations (2011)
Starches obtained from four Dioscorea species namely Dioscorea dumetorum (Bitter), Dioscorea oppositifolia (Chinese), Dioscorea alata (Water), and Dioscorea rotundata (White) have been evaluated as binding agents in chloroquine phosphate tablet formulations in comparison with official corn starch. The compressional properties of the formulations were analyzed using density measurements and the Heckel and Kawakita equations. The mechanical properties of the tablets were assessed using tensile strength, brittle fracture index (BFI), and friability tests while the drug release properties of the tablets were assessed using disintegration and dissolution times. The results indicate that the four starches vary considerably in their physicochemical properties. The ranking for the tensile strength and the disintegration and dissolution times for the formulations was Chinese> Bitter > Corn> White > Water while the ranking was reversed for BFI and friability. The results suggest that Water, White, and Corn could be useful when faster disintegration time of tablets is desired while Chinese and Bitter could be more useful when bond strength is of concern and in minimizing the problems of lamination and capping in tablet formulation